2016
DOI: 10.1002/ange.201601564
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Macrocyclization of 1,2,3‐Triazole Peptide Mimetics

Abstract: The macrocyclization of linear peptides is very often accompanied by significant improvements in their stability and biological activity. Many strategies are available for their chemical macrocyclization, however, enzyme‐mediated methods remain of great interest in terms of synthetic utility. To date, known macrocyclization enzymes have been shown to be active on both peptide and protein substrates. Here we show that the macrocyclization enzyme of the cyanobactin family, PatGmac, is capable of macrocyclizing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…After 16 h of reaction both 13mer and 14mer substrates produce similar amounts of macrocycle, but the 14mer generates less linear product. Linear peptide produced this may not be a significant drawback, as purification of macrocycles from liner peptides is straightforward 12 , 38 . Compared to PatG this represents a significant improvement, since biocatalytic reactions with PatG in vitro can require over 7 days and utilize up to stoichiometric amounts enzyme 12 , 38 .…”
Section: Discussionmentioning
confidence: 99%
“…After 16 h of reaction both 13mer and 14mer substrates produce similar amounts of macrocycle, but the 14mer generates less linear product. Linear peptide produced this may not be a significant drawback, as purification of macrocycles from liner peptides is straightforward 12 , 38 . Compared to PatG this represents a significant improvement, since biocatalytic reactions with PatG in vitro can require over 7 days and utilize up to stoichiometric amounts enzyme 12 , 38 .…”
Section: Discussionmentioning
confidence: 99%
“… 50 No macrocyclase enzyme has been engineered to improve or diversify function, although their natural substrate promiscuity has been exploited. 14 19 , 51 This is the first kinetic characterization of a macrocyclase and a necessary step toward designing a better catalyst for macrocyclization.…”
Section: Discussionmentioning
confidence: 99%
“… 10 PatGmac has been shown to be a highly versatile tool in the production of cyclic peptides. 14 16 However, PatGmac reactions are very slow in vitro , 11 although addition of reductant to Escherichia coli cultures improves production of the cyclic peptide patellin using the homologous tru enzymes by multiple orders of magnitude. 17 Butelase 1 is remarkably fast and effective as a tool for producing large peptide macrocycles, 18 20 but it cannot effectively cyclize peptide substrates containing nine or fewer amino acids.…”
mentioning
confidence: 99%
“…Furthermore, the initial pathway enzymes are highly conserved in sequence despite the great diversity of core peptides [35,40]. These observations have been used to prepare non-natural variants starting from precursor peptides containing the conserved RSs flanking hypervariable core regions [34,35,[42][43][44][45][46][47]. The following sections discuss how the biosynthetic enzymes involved in the biosynthesis of the cyanobactins as well as a subclass of lanthipeptides called the prochlorosins achieve the very high level of chemical diversity in their pathway products.…”
Section: Trends Trends In In Chemistry Chemistrymentioning
confidence: 99%
“…The leader peptide engages a domain in these enzymes called the RiPP recognition element (RRE) that is found in about half of all RiPP biosynthetic gene clusters [88]. Binding of the leader peptide to the RRE allows enzymatic azoline formation that is nearly insensitive to flanking residues [43,44,46,87,89]. For both lanthipeptide and cyanobactin biosynthetic enzymes, it has been shown that attachment of the leader peptide to the enzyme results in the processing of leaderfree core peptide, suggesting that leader peptide binding serves as an allosteric regulation mechanism and can work trans-acting [43,87,90,91].…”
Section: Diversity-generating Biosynthesis Of Cyanobactinsmentioning
confidence: 99%